Reverse breast lift for treatment of congenital symmastia - Getúlio Duarte Junior; Fábio Coelho Duarte (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Breasts are associated with a feeling of beauty, self-esteem, and female sexuality. Symmastia is a condition, characterized by the confluence of both breasts in the pre-sternal region. The author demonstrates a surgical technique for correction of congenital symmastia. METHODS: This is the case report of a young patient with previous history of breast hypertrophy and symmastia. She had previously undergone two mammoplasties and one liposuction of the breast, without correction of the symmastia . The author performed resection of the excess tissue in the breast and a reverse lifting of this region, with an upper abdominal advancement flap. RESULTS: There was complete resolution of the symmastia. CONCLUSION: The treatment performed by the author is a safe surgical alternative for the treatment of symmastia.